Calcium and chemical looping technology for power generation and carbon dioxide (CO2) capture - Fennell, Paul; Anthony, Ben (Amsterdam : Elsevier Ltd., 2015)
Calcium and Chemical Looping Technology for Power Generation and Carbon Dioxide (CO2) Capture reviews the fundamental principles, systems, oxygen carriers, and carbon dioxide carriers relevant to chemical looping and combustion. Chapters review the market development, economics, and deployment of these systems, also providing detailed information on the variety of materials and processes that will help to shape the future of CO2 capture ready power plants. Reviews the fundamental principles, systems, oxygen carriers, and carbon dioxide carriers relevant to calcium and chemical loopingProvi.
Part One. Introduction to calcium and chemical looping technology -- Part Two. Fundamentals of calcium looping technology -- Part Three. Fundamentals of chemical looping combustion technology -- Part Four. Advanced concepts and developments in calcium and chemical looping.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 20, 2015).
Elsevier
Keywords: Carbon sequestration; Electric power production; Fluidized-bed combustion; TECHNOLOGY & ENGINEERING / Environmental / General; Carbon sequestration; Electric power production; Fluidized-bed combustion; Electronic books